Flipped Classroom for Diving Environment Training Using Cooperative Learning - Wikanda, Egi; Siregar, Eveline; Wirasti, RA Murti Kusuma (Journal of Education Technology, 2021)
Diving training at Basarnas is constrained by distance so that it has an impact on the performance of employees' duties as individuals. This study aims to develop a flipped classroom for diving environment training for rescuers and obtain results to assess their feasibility. This study produces a research design and learning development with steps and procedures, namely using a multimedia-based learning design with stages ranging from assessment and needs analysis, design, development, implementation and evaluation. The techniques used to analyze the data are qualitative and quantitative analysis. The development steps taken refer to the web-based learning design combined with the PEDATI model at the design stage. The feasibility test is obtained based on the assessment of experts including material experts, learning design experts and media experts as well as testing for users to get suggestions for improvement. From the results of this study, it was found that the evaluation of training material experts with a total percentage value of 94.79%, expert validation of learning design 90.27%, and validation by instructional media experts 90.38%. The results of the individual one-to-one test are concluded to be very valid and can be used without revision, and for tests in small groups the average assessment is very valid without revision. It can be concluded that Flipped Classroom learning is suitable for use in diving environment training using cooperative learning.